Kolejny depozyt wiórów krzemiennych kultury pucharów lejkowatych (KPL) z Gródka nad Bugiem - Zakościelna, Anna (Polska Akademia Nauk. Instytut Archeologii i Etnologii, 1997)
S.95-108 : il. ; 25 cm
Streszcz. w jęz. ang.
Bibliogr. s. 105-107
Keywords: neolit -- Polska; pucharów lejkowatych kultura; osady kultury pucharów lejkowatych; przedmioty krzemienne kultury pucharów lejkowatych; wióry; Gródek, pow. Hrubieszów (Polska)

Materiały kultury pucharów lejkowatych ze stanowiska 1 w Radziejowie Kujawskim, woj. Włocławek - Rybicka, Małgorzata (Polska Akademia Nauk. Instytut Historii Kultury Materialnej, 1991)
S. 39-74 : il. ; 25 cm
Streszcz. w jęz. ang.
Bibliogr. przy tekście
Keywords: neolit -- Polska; pucharów lejkowatych kultura; ceramika kultury pucharów lejkowatych; ceramika kultury pucharów lejkowatych -- ornamentyka; ceramiki analizy; Radziejów Kujawski (Polska)

Badania sondażowe na osadzie kultury pucharów lejkowatych w Bronocicach, pow. Kazimierza Wielka, w 1969 r. - Burchard, Barbara (Zakład Narodowy im. Ossolińskich, 1975)
S. 65-94, [1] k. złoż. : il. ; 25 cm
Streszcz. w jęz. ang.
Bibliographical footnotes
Keywords: neolit -- Polska; sondażowe badania; pucharów lejkowatych kultura; osady kultury pucharów lejkowatych; ceramika kultury pucharów lejkowatych; Bronocice (Polska)

Typologia form naczyń kultury pucharów lejkowatych z obszaru Dolnego Śląska - Dreczko, Ewa (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2016)
The lack of a unified system of description of vessels types of the Funnel Beaker culture in Lower Silesia means that heterogeneous terminology prevents precise classification of ceramic forms found at sites of the culture. The paper presents a proposition of a classification of vessels types of the Funnel Beaker culture developed on the basis of analyses of artefacts from Lower Silesian sites. It has been constructed in a way that enables its complement in case of new discoveries, not falling within the present scope
il. ; 29 cm
Keywords: neolit; pucharów lejkowatych kultura; typologia; Śląsk Dolny

Sprawozdania Archeologiczne T. 33 (1982), Sesje i konferencje - Burchard, Barbara (Zakład Narodowy im. Ossolińskich, 1982)
Sympozjum w Rydzynie na temat "Kultura pucharów lejkowatych w Polsce" 23-25 X 1979 r.
S. 283 ; 25 cm
Keywords: konferencje archeologiczne; neolit -- Polska; pucharów lejkowatych kultura

Badania osady kultury pucharów lejkowatych w Gorzowie Wlkp. w latach 1975-1979 - Szczurek, Tadeusz (1944– ) (Zakład Narodowy im. Ossolińskich, 1982)
S. 19-29 : il. ; 25 cm
Streszcz. w jęz. ang.
Bibliogr. przy tekście
Keywords: neolit -- Polska; pucharów lejkowatych kultura; osady kultury pucharów lejkowatych; ceramika kultury pucharów lejkowatych; przedmioty krzemienne kultury pucharów lejkowatych; Gorzów Wielkopolski (Polska)

Wyniki dotychczasowych badań na stanowisku 1 w Kawczycach, woj. Kielce. Osada kultury pucharów lejkowatych - Nowak, Marek (Polska Akademia Nauk. Instytut Archeologii i Etnologii, 1994)
S. 115-134 : il. ; 25 cm
Streszcz. w jęz. ang.
Bibliogr. s. 133
Keywords: neolit -- Polska; pucharów lejkowatych kultura; osady kultury pucharów lejkowatych; ceramika kultury pucharów lejkowatych; przedmioty krzemienne kultury pucharów lejkowatych; Kawczyce, gm. Busko-Zdrój (Polska)

Stratyfikowany obiekt kultury pucharów lejkowatych w Gródku nad Bugiem, woj. zamojskie - Kokowski, Andrzej (Polska Akademia Nauk. Instytut Archeologii i Etnologii, 1995)
S. 137-156, [1] k. złoż. : il. ; 25 cm
Streszcz. w jęz. ang.
Bibliogr. przy tekście
Keywords: neolit -- Polska; pucharów lejkowatych kultura; osadnictwo kultury pucharów lejkowatych; ceramika kultury pucharów lejkowatych; przedmioty krzemienne kultury pucharów lejkowatych; Gródek, pow. Hrubieszów (Polska)

Neolithic Textile Production Artifacts at Bronocice - Pipes, Marie-Lorraine; Kruk, Janusz; Milisauskas, Sarunas (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2018)
The first evidence for fiber and textile production appeared around 5500 BC with the advent of Linear Pottery culture in southeastern Poland. By the fourth millennium BC, agricultural societies were well established and becoming increasingly sophisticated. Around 3700 BC the settlement of Bronocice began to develop economically, politically and technologically. From that time until the settlement collapsed around 2900 BC fiber and cloth production increased in scale. Unfortunately, there are few traces of textiles and no artistic representations exist of clothes worn by people living at the site. Instead, the proof lies in sheep skeletal remains, bone tools and clay artifacts
il. ; 25 cm
Keywords: neolit; pucharów lejkowatych kultura; produkcja tkanin i włókien; Bronocice

Cmentarzyska kultury pucharów lejkowatych w rejonie Sandomierza. Odkrycia 1971 roku - Tabaczyńska, Eleonora (Zakład Narodowy im. Ossolińskich, 1973)
S. 49-60 : il. ; 25 cm
Streszcz. w jęz. ang.
Bibliogr. przy tekście
Keywords: neolit -- Polska; pucharów lejkowatych kultura; cmentarzyska kultury pucharów lejkowatych; konstrukcje grobów kultury pucharów lejkowatych; wyposażenie grobów kultury pucharów lejkowatych; Sandomierz-region (Polska)

Chronology of the Funnel Beaker Culture Settlement in Western Ukraine in the Context of Radiocarbon Dating - Rybicka, Małgorzata (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2019)
The article concerns the absolute dating of the Funnel Beaker culture over the upper Bug and the upper Dniester (Polish-Ukrainian borderland and western Ukraine). Also discussed are the relations of the community of this culture from the eastern zone of the south-eastern group with the Tripolye culture.
il. ; 24 cm
Keywords: archeologia -- czasopisma

Bronocice Funnel Beaker Vessel with Wagon Motif: Different Narratives - Milisauskas, Sarunas; Kruk, Janusz; Hudson, Kathryn (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2019)
Excavations at the Polish site of Bronocice uncovered a vessel with a wagon motif in a late Funnel Beaker pit that dates to 3405 BC and also contained animal bones, flint artefacts and potsherds typical of the Funnel Beaker phase BR III. This article introduces the Bronocice site, provides an overview of the Bronocice vessel and its imagery, and presents some of the significant interpretations of the vessel. It also briefly considers the issues inherent in interpretation of ancient imagery and suggests ways to avoid imposing modern paradigms on ancient imagery.
il. ;24 cm
Keywords: archeologia -- czasopisma

Tomb no. 1 at Malżyce, site 31 (distr. Kazimierza Wielka) and the megalithic Funnel Beaker cemeteries in the loess region of western Małopolska = Grobowiec nr 1 na stanowisku 31 w Malżycach, pow. kazimierski i cmentarzyska megalityczne kultury pucharow lejkowatych na obszarach lessowych zachodniej Małopolski - Jarosz, Paweł; Szczepanek, Anita; Włodarczak, Piotr (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2013)
The remains of a heavily eroded Funnel Beaker tomb was discovered at Malżyce, site 31. At the centre of the excavation trench was the central burial with ditches, to the north and south of it, aligned W-E (features 2 and 3), and also, part of a broad depression — where earth was extracted and used to build up the burial mound (feature 7). To the east of the central burial were features 5 and 6, interpreted as elements belonging to the construction of the front end of the tomb. Feature 1, the central burial, was a stone structure, the grave pit held the remains of a maturus individual of undetermined sex. The absolute date obtained for the inhumation is 4765±35 BP which corresponds to 3641–3382 BC. These dates are compatible with the age estimated for the settlement finds attributed to the “classic phase” of development of the Funnel Beaker Culture in the loess upland of south-eastern Poland
il. ; 25 cm
Keywords: Malżyce; cmentarzyska kultury pucharów lejkowatych; grobowce megalityczne

Grobowce kultury pucharów lejkowatych w ujęciu polskiej archeologii neolitu = Tombs of the Funnelbeaker culture from the perspective of Polish Neolithic archaeology - Adamczak, Kamil (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2009)
30 cm
Keywords: neolit -- Polska; pucharów lejkowatych kultura; megality kultury pucharów lejkowatych; archeologia neolitu -- koncepcje polskie

Kultura pucharów lejkowatych w dorzeczu górnej Odry, Janina Bukowska-Gedigowa, „Przegląd Archeologiczny”, 23:1975, s. 83-186 : [recenzja] - Pavelčik, Jiři (Polska Akademia Nauk. Instytut Historii Kultury Materialnej, 1977)
29 cm
Keywords: neolit -- Polska; pucharów lejkowatych kultura; osadnictwo kultury pucharów lejkowatych; Śląsk Górny (Polska)

Beiträge zur frühneolithischen Trichterbecherkultur im westlichen Ostseegebiet, red. Jürgen Hoika, Jutta Meurers-Balke, Neumünster 1994 : [recenzja] - Wierzbicki, Jacek (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 1997)
29 cm
Keywords: neolit -- Bałtyku region; neolitu kultury; pucharów lejkowatych kultura; chronologia kultury pucharów lejkowatych

Naczynia neolityczne z Borkowa, w pow. inowrocławskim - Kostrzewski, Józef (1885–1969) (Polskie Towarzystwo Prehistoryczne, 1920)
il. ; 29 cm
Keywords: Poznańskie Towarzystwo Przyjaciół Nauk (Poznań, Polska). Muzeum; neolit -- Polska; pucharów lejkowatych kultura; ceramika kultury pucharów lejkowatych

Naczynie neolityczne z Poznania - Kostrzewski, Józef (1885–1969) (Polskie Towarzystwo Prehistoryczne, 1920)
il. ; 29 cm
Keywords: neolit --Poznań; pucharów lejkowatych kultura; ceramika kultury pucharów lejkowatych; Poznań, woj. wielkopolskie (Polska)

Dwa naczynia kultury pucharów lejkowatych z Łękna w pow. [powiecie] średzkim - Lipińska, Aleksandra (Polskie Towarzystwo Prehistoryczne, 1951)
il. ; 29 cm
Keywords: neolit -- Polska; pucharów lejkowatych kultura; ceramika kultury pucharów lejkowatych; Łękno, gm. Zaniemyśl (Polska)

Cmentarzysko grobowców kujawskich w Wietrzychowicach, pow. Koło - Makiewicz, Tadeusz (Zakład Narodowy im. Ossolińskich, 1969)
S. 25-28 : il. ; 25 cm
Streszcz. w jęz. ang.
Bibliogr. przy tekście
Keywords: neolit -- Polska; pucharów lejkowatych kultura; cmentarzyska kultury pucharów lejkowatych; grobowce typu kujawskiego; megality; Wietrzychowice (Polska)

Konary, gm. Dąbrowa Biskupia, woj. Bydgoszcz, stan. 6A-6B (przyczenek do studiów nad "centralnokujawskim" nurtem technologicznego i stylistycznego rozwoju ceramiki kultury pucharów lejkowatych) - Prinke, Danuta (Zakład Narodowy im. Ossolińskich, 1983)
S. 25-51 : il. ; 25 cm
Streszcz. w jęz. ang.
Bibliogr. przy tekście
Keywords: neolit -- Polska; osadnictwo neolitu; pucharów lejkowatych kultura; ceramika kultury pucharów lejkowatych; Kujawy (Polska); Konary (Polska)

"Skarb" naczyń glinianych z Jakubowic Murowanych, woj. Lublin, na tle innych znalezisk gromadnych - Bargieł, Barbara (Zakład Narodowy im. Ossolińskich, 1989)
S. 57-62 : il. ; 25 cm
Streszcz. w jęz. ang.
Bibliogr. przy tekście
Keywords: neolit -- Polska; pucharów lejkowatych kultura; ceramika kultury pucharów lejkowatych; Jakubowice Murowane (Polska)

Skład wiórów krzemiennych kultury pucharów lejkowatych z Wincentowa, stanowisko 5, gm. Krasnystaw, woj. Chełm - Kadrow, Sławomir (1956– ) (Zakład Narodowy im. Ossolińskich, 1989)
S. 27-33 : il. ; 25 cm
Streszcz. w jęz. ang.
Bibliogr. przy tekście
Keywords: neolit -- Polska; pucharów lejkowatych kultura; przedmioty krzemienne kultury pucharów lejkowatych; wióry; Wincentów (Polska)

Bezkomorowy grobowiec megalityczny (tzw. kujawski) w Krępcewie nad Iną, stan. 4, gm. Kolin, woj. Szczecin - Wiślański, Tadeusz (1931–1989) (Zakład Narodowy im. Ossolińskich, 1977)
S. 83-100, [1] k. złoż. : il. ; 25 cm
Streszcz. w jęz. ang.
Bibliogr. przy tekście
Keywords: neolit -- Polska; pucharów lejkowatych kultura; cmentarzyska kultury pucharów lejkowatych; megality neolitu; grobowce typu kujawskiego; Krępcewo (Polska)

Pozycja stratygraficzna materiałów kultury pucharów lejkowatych na stanowisku Mogiła 62 w Nowej Hucie - Kaczanowska, Małgorzata (Zakład Narodowy im. Ossolińskich, 1976)
S. 89-99 : il. ; 25 cm
Streszcz. w jęz. ang.
Bibliogr. przy tekście
Keywords: neolit -- Polska; stratygrafia; pucharów lejkowatych kultura; osadnictwo kultury pucharów lejkowatych; Mogiła (Kraków, Polska); Kraków (Polska)